2011
DOI: 10.1038/nm.2449
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK–mediated regulation of Xbp1s is crucial for glucose homeostasis

Abstract: Here we show that p38 mitogen activated protein kinase (p38 MAPK) phosphorylates spliced form of X-Box Binding Protein 1 (XBP1s) on Thr48 and Ser61 residues and greatly enhances nuclear migration of XBP1s. Mutation of Thr48 and Ser61 to alanine dramatically reduces nuclear translocation of XBP1s and activity. We also demonstrate that p38 MAPK activity is markedly reduced in the livers of obese mice and that activation of p38 MAPK by expression of constitutively active MAP Kinase Kinase 6 (MKK6Glu) greatly enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
176
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(188 citation statements)
references
References 50 publications
10
176
0
2
Order By: Relevance
“…6A) but not at 3 months of age (data not shown). When ER stress was induced by 1-h refeeding after the 24-h fasting period, according to a previously reported ER stress paradigm (30), abnormal increases in the phosphorylation of IRE1a (Fig. 6B) and JNK (Fig.…”
Section: Orexin-induced Daily Glucose Rhythm Prevents Er Stress and Hsupporting
confidence: 58%
“…6A) but not at 3 months of age (data not shown). When ER stress was induced by 1-h refeeding after the 24-h fasting period, according to a previously reported ER stress paradigm (30), abnormal increases in the phosphorylation of IRE1a (Fig. 6B) and JNK (Fig.…”
Section: Orexin-induced Daily Glucose Rhythm Prevents Er Stress and Hsupporting
confidence: 58%
“…It also has yet to be dissected how XBP1s can be delicately regulated in vivo to control different sets of gene expression programs under these circumstances. It warrants further investigation whether XBP1s may act as a molecular regulatory switch through acetylation 37 , phosphorylation 15 or other modifications under anabolic versus catabolic conditions. In summary, our findings indicate that hepatic IRE1a serves as a crucial component of the nutrient-sensing machinery that regulates the metabolic adaptive response to starvation.…”
Section: Xbp1s Normalizes the Metabolic Impairment Inmentioning
confidence: 99%
“…Studies in animal models have implicated IRE1a or XBP1s in both glucose and lipid metabolism 6,8,9,[13][14][15][16][17][18][19][20] . Recently, it was shown that the hepatic IRE1a-XBP1 pathway is activated upon refeeding, and overexpression of XBP1s in livers of mice may promote postprandial metabolic changes 6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reinstating the hepatic activity of XBP1s reduced ER stress and improved glucose homeostasis through mechanisms that are both dependent (14,15) and independent of XBP1s transcriptional activity (16). This indicates that XBP1s is indispensable for the maintenance of glucose homeostasis in obesity.…”
mentioning
confidence: 91%